Phyllanthus amarus Does Not Affect Hypernociception in Experimental Autoimmune Encephalomyelitis - Molska, Graziella Rigueira; Negri, Giuseppina; Paula-Freire, Lyvia Izaura Gomes; Araujo, Leandro Pires; Köhn, Daniele Oliveira; Basso, Alexandre Salgado; Carlini, Elisaldo Araújo (Planta Medica, 2014)
Multiple sclerosis is an inflammatory disease of the central nervous system. Chronic pain is one of the main symptoms, affecting many patients. Studies show that the lignans or the apolar extracts of Phyllanthus amarus have antinociceptive effects in different animal models. To evaluate the antihypernociceptive effect of a hexanic extract of P. amarus in experimental autoimmune encephalomyelitis in mice, the chemical composition of the hexanic extract was analyzed by gas chromatography mass spectrometry. After EAE induction, animals were treated with the hexanic extract of P. amarus for 26 consecutive days. Motor coordination and mechanical hypernociception were evaluated on alternate days. The principal lignans found were phyllanthin, niranthin, and 5-demethoxyniranthin. The hexanic extract of P. amarus at a dose of 100, 200, or 400 mg/kg did not affect the development of the disease. The motor coordination and pain threshold of the treated animals were not altered in this experiment. In conclusion, in this test, the hexanic extract of P. amarus did not show evidence of antihypernociceptive activity in experimental autoimmune encephalomyelitis.
Keywords: Phyllanthus amarus; Euphorbiaceae; pain; hypernociception; experimental autoimmune encephalomyelitis; lignans